Job satisfaction and sources of work pressure on college professors in Metropolitan Lima - Álvarez-Flores, David (2007)
This correlational research sought to investigate the relationship between the sources of work pressure and job satisfaction among university professors in metropolitan Lima. In this study it was used a cross-sectional correlational design. The sample consisted of 506 university professors selected by clusters. The following instruments were used: Personal Data Questionnaire, Teaching Satisfaction Scale using a Lickert-type scale, and an Inventory of Teaching Work pressure. The instruments showed construct validity and internal consistency reliability. The findings show that sources of work pressure and job satisfaction  are inversely related.